2019
DOI: 10.21037/atm.2019.11.54
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient burden of gastric cancer in the United States

Abstract: Background: Gastric cancer is associated with significant morbidity and mortality. Over one-half of patients have advanced disease at the time of presentation, leading to a significant burden on the healthcare system. Limited epidemiological data exists on national inpatient hospitalization trends. The aim of this study is to determine the inpatient burden of gastric cancer in the United States.Methods: We analyzed the Nationwide Inpatient Sample (NIS) database for all subjects with the diagnosis of malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Our results also showed that the cytoplasmic HuR was strongly decreased due to 5-FU, which indicates a negative regulatory role of HuR in gastric cancer. Conversely, in a previous study, HuR expression levels were reported to be significantly enhanced upon 5-FU stimulation in breast cancer cells (2). 5-FU induces the cytoplasmic export of HuR in pancreatic cancer (30).…”
Section: Discussionmentioning
confidence: 64%
“…Our results also showed that the cytoplasmic HuR was strongly decreased due to 5-FU, which indicates a negative regulatory role of HuR in gastric cancer. Conversely, in a previous study, HuR expression levels were reported to be significantly enhanced upon 5-FU stimulation in breast cancer cells (2). 5-FU induces the cytoplasmic export of HuR in pancreatic cancer (30).…”
Section: Discussionmentioning
confidence: 64%
“…This reduces bias seen in studies which are confined to one hospital or region. 52 However, our analysis has some limitations. We could not differentiate the hospitalizations with a new diagnosis of paralytic ileus from the old hospitalizations.…”
Section: Discussionmentioning
confidence: 96%
“…The data are compiled yearly and contain discharge information from over 1,200 hospitals located across the states [ 7 ]. The internal validity of the database is guaranteed by the annual data quality assessments, while comparisons with data sources like the American Hospital Association (AHA) Annual Survey of Hospitals, National Hospital Discharge Survey from the National Center for Health Statistics, and Medicare Provider and Analysis Review (MedPAR) inpatient data from the Centers for Medicare and Medicaid Services guarantee the external validity [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used the Cochran-Armitage trend test to calculate the trends for categorical variables and Wilcoxon rank sum test to assess continuous variables. These methods have been used in previous NIS-based studies [ 8 , 10 , 11 ]. We used the multivariate logistic regression model to determine predictors of mortality.…”
Section: Methodsmentioning
confidence: 99%